Toxic effects of Fe2WO6 nanoparticles towards microalga Dunaliella salina: Sonochemical synthesis nanoparticles and investigate its impact on the growth. (November 2020) - Hassanpour, Mohammad; Hosseini Tafreshi, Seyed Ali; Amiri, Omid; Hamadanian, Masood; Salavati-Niasari, Masoud
Abstract: In this work, Fe2 WO6 nanoparticles were synthesized by the ultrasound-assisted precipitation method. Various conditions were applied, including the change of the pH factor and reaction time for the synthesis of nanoparticles. After confirming the synthesis of the nanoparticles by various analyzes and evaluating their size and morphology, one of the conditions for the synthesis of the nanoparticles were selected as the optimum condition. The samples were added to the growth medium of a well-known microalga, Dunaliella salina at three concentrations of 20, 40 and 80 ppm to evaluate the effect of nanoparticles on biological systems. After 10 days different biological parameters were measured and compared with those of the control sample. According to the results, at concentration of 20 ppm the number of cells, the amount of chlorophyll a, and b, and biomass increased compared to the control samples. The Carotenoid level was higher in the treatment with 40 ppm of nanoparticles than that in the control samples. Compared to the control sample, the level of lipid peroxidation and the ratio of carbohydrate to amide II showed to be higher under 80 ppm treatment of particles. According to HCA analysis, both the evaluated parameters and concentrations of nanoparticles were divided into two general categories. Overall results showed that the effect of Fe2 WO6 nanoparticles on microalgae could be a dose-dependent phenomenon, so that the addition of 20 ppm nanoparticles in the culture media helped the growth and the physiological status of algae. On the other hand, the application of a higher concentration of nanoparticles negatively affects algal biology. The results showed that the algae could be successfully used to precise screen of various nanoparticles in terms of safety especially in aquatic environments and also biotechnological applications. Graphical abstract: Image 1 Highlights: Synthesis Fe2 WO6 nanoparticles by ultrasound-assisted precipitation methods. The ultrasound-assisted method as a fast and simple were chosen as an optimum method. The optimum sample were selected after applying different pH adjustment and reaction times. The optimum sample were used for investigation of Fe2 WO6 effects on Dunaliella salina for the first time. The biological surveys various parameter were measured on alga.